Marburg and Ravn Viruses Fail to Cause Disease in the Domestic Ferret (Mustela putorius furo). (28th June 2018) - Cross, Robert W; Mire, Chad E; Agans, Krystle N; Borisevich, Viktoriya; Fenton, Karla A; Geisbert, Thomas W
Abstract: The domestic ferret was recently described as a uniformly lethal model for 3 species of Ebolavirus . More importantly, this new model utilizes nonadapted wild-type Ebolaviruses . Here, in a proof-of-concept study, we infected ferrets with different variants of the closely related Marburg and Ravn viruses using different doses and routes of exposure. Although ferrets produced a neutralizing humoral response to challenge, we did not observe disease or viremia in any animal. The lack of disease in ferrets underscores the notion that differential mechanisms to immunity among filoviruses exist and may provide a model to better understand how differences contribute to disease.